Study Characteristic Thermal Electric Generator (TEG) Type SP1848 27145 SA - Sofia Debi Puspa; I Putu Budi Dharma; Sentot Novianto; Supriyadi; M. Alfian Gibran (Fakultas Teknik Universitas Pancasila, 2024)
The TEG component, which operates on the Seebeck principle like a thermocouple, is widely used in the market, with TEG SP1848 27145 SA being one of the most common types. However, experiments must be conducted to determine its Seebeck coefficient, voltage, and power output when used with different heat and cold sources. This research aims to observe how the Seebeck coefficient, voltage, and power output of TEG SP1848 27145 SA change with variations in system temperature. To experiment, TEG SP1848 27145 SA is tested with a heater, and water flow rates are varied for cooling. Furthermore, the correlation between output voltage and ΔT has been determined through statistical analysis. The experiment results showed that the voltage output ranged from 0.54–1.03 V at a heater temperature of 86°C and an ΔT system value of 70.5-75°C. The Seebeck value was between 1,551.7-2,998.5 µV, and the power output was 43.5-67.7 mW. Additionally, the statistical analysis found a significant correlation between the temperature variable and output voltage variable, with an adjusted r square value of 89.2% for zero water flow rate and increasing to 95.8% for maximum water flow rate.